(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Since ancient times, travelers from various regions have visited various parts of India, in pursuit of migration, trade, and invasion. India was a land of resources to them, with its famous Indian culture, capital, religious faiths, belief systems, art, architectural style, academic practices as well as a plethora of natural resources and climatic conditions spreading all over. Absorbing the traits of well-managed, self-confidence and enormous values will assist every individual in earning a remarkable place in society. Education without values is akin to beauty without virtue, which is like a flower without fragrance or a body without a soul. Society should recognize that developing one’s moral character is just as important as developing one’s career. In life, a moral character is an ultimate thing that bridges a person’s self-realization. The ancient Indian education system was regarded as a repository of awareness, customs, and practices that directed and inspired humanity. Value-based education helps students by preparing them to face the world with the right values and attitudes. With the help of this process, students’ overall personality development is possible. As a result, scholars exposed to a value-based education system develop character, personality, citizenship, and spirituality. In this review article, an attempt has been made to draw attention towards the prevailing value-based education system in ancient India, with the help of a critical literature review by following the PRISM approach. The findings not only suggest but also recommend the value-based education system for inclusion in education policies so that value-based systems can help for holistic development of our future generations and make a peaceful and sustainable society.